PENGARUH KUALITAS LAYANAN DAN CITRA MEREK PADA LOYALITAS PELANGGANDISTRO HOUSE OF SMITH SEMARANG - ShabrinaFarah Gassani, 11.05.51.0023; Yulianto, Heru (Students Journal of Economic and Management, 2015)
The purpose of this study to analyze the effect of service and brand image on customer loyalty distributions House of Smith Semarang. The population of this study is that consumers on the distributions House of Smith Semarang who never made a purchase of at least 3 period. The sampling technique used in this study is purposive sampling with a sample of 80 respondents. Analysis of this data using multiple regression. The results showed that the quality of service and a positive brand image and significantly influential on customer loyalty. Keywords: Service Quality, Brand Image, Customer Loyalty